Higher-Order Cognition in Personalised Adaptive eLearning - MACARTHUR, VICTORIA; CONLAN, OWEN (My University, 2008)
In nature, the Goby fish lives in symbiosis with the burrowing shrimp; serving as a watchman in return for a place to live. Current adaptive learning systems hold an ambiguous position that attempts to compensate for real-world interaction. This paper presents a novel symbiotic-dialog approach to abstract cognitive skill training. The approach is implemented within Goby, a third-party symbiotic service that will support the acquisition of a metacognitive repertoire, within the context of a host eLearning system.
International Workshop on Cognitive Aspects in Intelligent and Adaptive Web-based Educational Systems held at the 16th International Conference on Computers in Education (ICCE08)
PUBLISHED
Taiwan
Keywords: Metacognition; Adaptive Services; Personalisation; eLearning